Elementary students’ worksheet based on discovery learning for environmental education and biodiversity learning - Ichsan, Ilmi Zajuli; Susanto, Lufty Hari; Ali, Ahmad; Merliana, Anggit (Jurnal Mangifera Edu, 2024)
The discussion of environmental issues and the biodiversity of flora and fauna are interesting topics to remarkable. This topic includes the learning process at the elementary school level. The learning tool that can be developed is student worksheets for elementary schools. The objective of this research is to develop discovery learning-based student worksheets for elementary school students on environmental and biodiversity topics. The ADDIE model was employed as the research methodology in this study. The development stages carried out are starting from analysis, design, development, implementation, and evaluation. The data analysis used was descriptive. The results of the research show that the student worksheet developed has a very valid category and is appropriate for use in learning with detail scores from Learning Expert I (3.90), Learning Expert II (3.70), and Learning Expert III (3.90). Students' worksheets were very valid and appropriate for learning. Student worksheets are one of the innovations that can be developed in school. The results of this research further validate that the student worksheets employed in fostering the development of student's critical thinking and creative thinking abilities. This research concludes that student worksheets based on discovery learning in environmental and biodiversity topics are appropriate for educational purposes.